Teachers Creativity and its Specific Expression in Educational Process - Grakauskaitė - Karkockienė, Daiva (Pedagogika, 2016)
The article discusses different aspects of teachers’ creativity and its specific expression in educational process. In Lithuania it is the first research focused on relationship between different aspects of teachers’ creativity and their views about its nature. The aim of this research – to explore relationship between specific aspects of teachers’ creativity (divergent thinking, nonconformity, persistence and intrinsic motivation) and teachers’ qualification as well as pedagogical experience. The questionnaire for evaluation of creativity was made for this study (Cronbach alpha – 0,848). The research involved 102 teachers from Vilnius and Marijampole districts, including 78 females and 24 males having university education. Teachers have different qualification categories and different pedagogical experience. The results of the research have shown that a higher qualification category as well as a longer pedagogical experience are related to higher estimates of divergent thinking, nonconformity, intrinsic motivation, but are not related to the persistence. The teachers were asked also if creativity is a gift or if it could be developed. It’s important to study this topic because on it depends the education of students’ creativity at schools. It has been revealed that teachers with a higher qualification category as well as a longer pedagogical experience more often believe that creativity could be developed.